Assessment of multimodality therapy use for extremity sarcoma in the United States. Issue 5 (20th December 2013) - Sherman, Karen L.; Wayne, Jeffrey D.; Chung, Jeanette; Agulnik, Mark; Attar, Samer; Hayes, John P.; Laskin, William B.; Peabody, Terrance D.; Bentrem, David J.; Pollock, Raphael E.; Bilimoria, Karl Y.
Abstract Background Extremity sarcoma national guidelines offer several stage‐specific treatment options; therefore, treatment approaches are not standardized. Our objectives were to examine multimodality treatment trends, practice patterns, and factors associated with neoadjuvant or postoperative adjuvant therapy utilization. Methods Using the National Cancer Data Base (2000–2009), treatment of non‐metastatic extremity sarcoma was examined. Regression models were developed to identify factors associated with neoadjuvant or postoperative adjuvant therapy receipt and treatment sequence. Results Twenty‐two thousand fifty‐one patients underwent resection (stage I: 45.2%, stage II: 27.7%, stage III: 27.1%). Over 10 years, neoadjuvant radiation (6.4–11.6%, P < 0.001) and chemotherapy utilization (1.4–1.8%, P = 0.037) increased, while postoperative radiation (34.3–29.2%, P = 0.023) and trimodality therapy decreased (10.5–9.6%, P = 0.002). After adjusting for age, comorbidities, and histology, patients with large high‐grade tumors treated at high‐volume academic centers were more likely to receive neoadjuvant therapy (all P < 0.001). Postoperative chemotherapy utilization was associated with younger age, synovial histology, high grade, and surgical margins (all P < 0.001). Conclusions Utilization of neoadjuvant therapy for extremity sarcoma has increased over time. Practice patterns are not only related to tumor size, grade, histology, and margins but also hospital type. Opportunities remain to better define the most effective multimodality treatment for extremity sarcoma. J. Surg. Oncol. 2014 109:395–404. © 2013 Wiley Periodicals, Inc.